Why is the use of support surfaces not more evidence based? - Draft paper or article for publication. Issue 1 (February 2021) - Hodgkinson, Ray; Clancy, Michael; Collyer, Graham
Highlights: This article explores some reasons for the dearth of evidence for therapeutic support surfaces in relation to pressure ulcer (PU) prevention and provides some insight into why more support surfaces are in use and highlights newer evidenced based technology now being adopted in the NHS and elsewhere. The 'Pressure 2' study (2019) identified some difficulties with producing evidence for the use of support surfaces including defining the primary purpose for their use, product selection, and intervention and raised concerns that the burden posed by the need for clinical studies to prove preference of one surface against another in preventing pressure ulcers may delay or terminate innovation in this key area, at least in England. Product identification and selection and important determinates: The NICE Guidance (cg179) and EPUAP/NPIAP/PPPIA Pressure Ulcer Guidance insistence upon using the term 'High Specification Foam Mattresses' is to perpetuate the myth that there is a material that is High Specification Foam. Manufacturers are reluctant to sponsor research because of the difficulty of obtaining evidence that meets MDR requirements and the historical slow adoption of innovation in the NHS. Indeed it appears that NICE are sceptical of 'evidence funded by industry'.